Automatic Calibration of Tank Model Using Microsoft Excel Solver - ศาสนนันทน์ เสฎฐา (Srinakharinwirot University Engineering Journal, 2018)
The objective of research is to determine optimal parameters of tank model using Microsoft Excel Solver. The parameters can be optimized and compared by using trial and error method and Microsoft Excel Solver. It can be concluded that model parameters using Microsoft Excel Solver showed better correlations more than that of trial and error method by increasing accuracy and convenience. The results showed that Microsoft Excel Solver can be used to calibrated Tank model parameter in Upper Yom River Basin. Additionally, for the research at hand, it was found that the best of objective function from the group of IA, Nash, R2 and RMSE is IA